Development strategy for natural tourism attractions: A SWOT analysis for sustainable growth - Astika, Aci; Indriyani, Lies; Siwi, La Ode; Bana, Sahindomi; Fahidu, Wa Ode Hastiani; Tuwu, Eka Rahmatiah; Gandri, La (Social, Ecology, Economy for Sustainable Development Goals Journal, 2025)
Background: This research aims to find out Development Strategy Te'ekuea Baths as a Natural Tourism Attraction in Maleko Village, Wangi-Wangi District, Wakatobi Regency. Methods: This research was conducted in October-November 2023 using interview observation, documentation and literature study methods. The population in this research is the entire community in Maleko Village. The population in this research is the community, related agencies and visitors who carry out activities at the Te'ekuea Bathing Tour. The sample chosen in this study was 10% of 177 heads of families (KK), so 10% of the number of family heads is 17.7 or rounded up to 18 families. Meanwhile, for sample determination, the method can be used accsidental sampling. Respondents who have been determined using the method purposive sampling. In this research purposive sampling addressed to the Tourism Department, Bappeda (planning agency development regional), village heads, sub-district heads and community leaders. The data analysis carried out in this research is qualitative and quantitative descriptive analysis to describe the SWOT analysis so as to obtain a tourism development strategy. Findings: The Te'ekuea Baths development strategy shows the highest opportunity in income increase (0.62) and the lowest threat in visitor disruptions (0.17). The SWOT matrix suggests four main strategies: S-O (maximize strengths for visitor attraction), W-O (improve promotion and facilities), S-T (manage eco-friendly waste and public awareness), and W-T (enhance cleanliness and facilities). The IFE matrix average score is 2.9, and EFE matrix is 2.78, indicating growth potential. Conclusions: The research emphasizes the vital role of modern digital promotion techniques, especially social media, in enhancing the visibility of Te'ekuea Baths as a tourism destination, ultimately driving greater engagement and visitor growth. Novelty/Originality of this article: This study highlights the role of modern digital promotion methods, such as websites and social media, in advancing local tourism, focusing on their effectiveness in engaging younger generations and broadening the reach of the Te'ekuea Baths tourism destination.